Determination of Optimal Fermentation Time in the Production of Liquid Organic Fertilizer from Tempe Liquid Waste with the Addition of Banana Peels - Muliati, Lia; Maelani, Rima; Khopipah, Salwa Nur (Universitas Insan Cendekia Mandiri, 2025)
The tempeh industry uses soybeans as the main raw material to produce the main product, namely tempeh. Based on observations of the local industry, tempeh production waste in the South Margahayu area is very high, because more than one factory produces tempeh waste. Utilization of waste materials as organic fertilizer is one way to overcome environmental pollution problems. Banana peels contain many substances and are beneficial for plants if processed into liquid organic fertilizer, because banana peels contain 42% potassium so that they can strengthen plant stems, fight diseases, and fertilize plants and flowers and fruit trees. This study uses 1 type of stage, namely the liquid organic fertilizer production process. Testing of liquid organic fertilizers made from liquid tempeh waste and banana peels was carried out to determine the suitability between the levels of macro nutrients produced from the liquid organic fertilizer with the standard quality of liquid organic fertilizers based on SNI. The analysis method in this study uses a quantitative method obtained from the results of measuring the levels of nutrients in raw materials and liquid organic fertilizers. The protein content in the results of the tempeh liquid waste test was 0.48%. The C-Organic content on the 7th day was 1.72%. On the 7th day, the nitrogen produced was 0.10%, phosphorus was 0.07%, and potassium was 0.62%. Based on the results of the study, the optimum fermentation time for the production of organic liquid fertilizers was on the 7th day with a total NPK content of 0.79%, C/N of 20 and C-organic 1.72%. The production of POC from tempeh liquid waste with the addition of banana peels has not produced macronutrient levels that are in accordance with the SNI standards for organic liquid fertilizers so that commercial production cannot be carried out. Many factors influence the process of forming this liquid organic fertilizer, including bioactivators, namely effective microorganisms commonly known as EM-4, temperature, sun intensity, humidity, production time and placement in the fertilizer production process.